2021
DOI: 10.1080/21655979.2021.1978196
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOXA-AS3 promotes cell proliferation of oral squamous cell carcinoma through sponging microRNA miR-218-5p

Abstract: Increasing evidence demonstrated long non-coding RNAs (lncRNAs) play important roles in the occurrence and development of oral squamous cell carcinoma (OSCC). This study aimed to explore the role and molecular mechanism of lncRNA HOXA-AS3 in the progression of OSCC. Here, we found that t he expression of lncRNA HOXA-AS3 was upregulated in OSCC tissues and cell lines compared with the para-cancerous tissues and normal human oral keratinocyte (NHOK), respectively. Inhibition of HOXA-AS3 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
5
14
0
Order By: Relevance
“…A previous report showed that LPCAT1 could facilitate OSCC cell invasiveness and proliferation via increasing the biosynthesis of platelet‐activating factors 37 . In addition, HOXA‐AS3 promoted OSCC cell proliferation via LPCAT1 38 . Our data showed an overt elevation in LPCAT1 expression in OSCC samples and cells.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A previous report showed that LPCAT1 could facilitate OSCC cell invasiveness and proliferation via increasing the biosynthesis of platelet‐activating factors 37 . In addition, HOXA‐AS3 promoted OSCC cell proliferation via LPCAT1 38 . Our data showed an overt elevation in LPCAT1 expression in OSCC samples and cells.…”
Section: Discussionsupporting
confidence: 67%
“…37 In addition, HOXA-AS3 promoted OSCC cell proliferation via LPCAT1. 38 Our data showed an overt elevation in LPCAT1 expression in OSCC samples and cells.…”
Section: Discussionsupporting
confidence: 50%
“…Although many studies have shown the involvement of lncRNAs in sepsis [ 19 , 20 ], the roles of most lncRNAs in this disease remain unclear and need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence showed that the overexpression of HOXA-AS3 was revealed in various types of human diseases and pathophysiological processes, including liver cancer [23][24][25], glioma [26,27], lung cancer [28][29][30], oral cancer [31], colorectal cancer [32], gastric cancer [33], pancreatic cancer [34], endometriosis [35], atherosclerosis [36,37], pulmonary arterial hypertension [38], and the lineage differentiation of mesenchymal stem cells (MSCs) [39]. In addition, high HOXA-AS3 expression has been identified to correlate with unfavorable clinicopathological features and poor prognoses, such as pathological grade, TNM stage, tumor size, lymph node metastasis, invasion depth, and Helicobacter pylori infection status, overall survival, and disease-free survival (Table 1).…”
Section: The Expression Of Hoxa-as3 and Its Roles In Human Diseases A...mentioning
confidence: 99%
“…lncRNA HOXA Cluster Antisense RNA 3 (HOXA-AS3) is a newly discovered lncRNA with 25,952 bases and in the genomic location at human chromosome 7p15.2 started 900 nt downstream of the 3' end of HOXB5 [22]. HOXA-AS3 expression has been implicated in a variety of human diseases and pathophysiological processes, including liver cancer [23][24][25], glioma [26,27], lung cancer [28][29][30], oral cancer [31], colorectal cancer [32], gastric cancer [33], pancreatic cancer [34], endometriosis [35], atherosclerosis [36,37], pulmonary arterial hypertension [38,39], and even the lineage differentiation of mesenchymal stem cells (MSCs) [39], according to numerous studies. In these disorders, high HOXA-AS3 expression has been reported to closely relate to several clinicopathologic characteristics, such as pathological grade, TNM stage, tumor size, lymph node metastasis, invasion depth, and Helicobacter pylori infection status, overall survival, and disease-free survival.…”
Section: Introductionmentioning
confidence: 99%